ANALISA LOGAM BESI (Fe) DI SUNGAI PASAR DAERAH BELANGWETAN KLATEN DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Rahmi Nurhaini; Arief Affandi (Jurnal Ilmiah Manuntung, 2016)
Iron (Fe) is one of many heavy metals that is corrosive resistant, dense, and has a low melting point. If accumulated in the body, the metal can cause some medical conditions, such as irritation to skin and eyes, breathing problems, and in the long term, cancer. This research aims to know generally the spread of metallic iron (Fe) in the river Pasar in Belangwetan, Klaten. This study was conducted using an observational method in which researchers did not examine the effects of interventions. Sampling was done using purposive sampling method taken from three points, namely the upper, middle, lower. Determination of iron levels by Atomic Absorption Spectrophotometer (AAS) obtained a positive result, and the data was processed using SPSS to determine the Mean and Standard Deviation. Of the research result, it could be known the Mean score was 2.33 ppm and SD was 0.0352. The result of this research indicated that the levels of iron in the river Pasar in Belangwetan were 2.33 ppm. It means that the levels violate the regulation of the Minister of Health of the Republic of Indonesia, which is not more than 1mg/L (1ppm) in the clean water